VARIABILITY OF SEA SURFACE CHLOROPHYLL-A, TEMPERATURE AND FISH CATCH WITHIN INDONESIAN REGION REVEALED BY SATELLITE DATA - Sachoemar, Suhendar (Marine Research in Indonesia, 2012)
The investigation of sea surface chlorophyll-a (SSC) and sea surface temperature (SST) in relation to fish catch variability within the Indonesian region were conducted by using satellite data of NOAA-AVHRR, SeaWiFs and Aqua MODIS. The investigation focused in the region of the coastal area of Java, Lampung Bay and South Kalimantan as representation of the environment diversities of the Indonesian seas. The result shows that seasonal variation in fish productivity has a strong correlation with SSC variability. High fish productivity corresponded well with high concentration of SSC, and the productivity tended to decrease when the SSC concentration was declined. High SSC variability in the coastal area of Java and Lampung Bay was governed by the upwelling that induced high nutrient load into the sea surface during the southeast monsoon, while in the northern coastal area of Java and South Kalimantan, it was governed by high precipitation ocurring during the northwest monsoon that enhanced the nutrient load through the rivers and coastal discharge.